Respuesta :

Wolfyy

Hey!

-----------------------------------------------

Solution:

-2 - 5p = 2p - 2 (Solve)

-2 - 5p + 5p = = 2p - 2 + 5p (Add 5p to both sides)

-2 = 7p - 2 (Simplify)

-2 + 2 = 7p - 2 + 2 (Add 2 to both sides)

0 = p

-----------------------------------------------

Check:

-2 - 5(0) = 2(0) - 2

-2 = -2

Inequality is true when p = 0!

-----------------------------------------------

Answer:

p = 0

-----------------------------------------------

Hope This Helped! Good Luck!

The answer is 0

Let's solve your equation step-by-step.

−2−5p=2p−2

Step 1: Simplify both sides of the equation.

−2−5p=2p−2

−2+−5p=2p+−2

−5p−2=2p−2

Step 2: Subtract 2p from both sides.

−5p−2−2p=2p−2−2p

−7p−2=−2

Step 3: Add 2 to both sides.

−7p−2+2=−2+2

−7p=0

Step 4: Divide both sides by -7.

−7p−7=0−7

p=0

Please give me brainliest if it is correct!

ACCESS MORE